3D building modelling reconstruction for sustainable safeguarding native Malay urban architectural in Malaysia - Hj. Mohd. Noor, Norzailawati; Abdullah, Ahmad Afiq Aiman; Abdullah, Alias (IOP Publishing, 2020)
Documentary works through the three dimensional reconstruction are the key part of our documentation system for cultural heritage conservation. It preserve and safeguarding all the visual information in order to provide access to future generations is at the core of the work of libraries globally. This paper attempt to reconstruct 3D GIS modelling for an indigenous Malay cities based on urban traditional settlement urban forms element known as building. Four building aspects of Malay settlements have been demonstrated at the selected genuine old traditional Malay settlement located at Kota Bahru Malaysia. 3D building Modelling has been performed based on building footprint that has been obtained from the data collected through integration of photogrammetry and GIS approach. The process of reconstruction animated urban features based on four main building aspects consist of height, surface, façade and location of the Malay settlements. The finding shows that, the elements of urban form based on building aspects has been proven as a part of basic fundamental to recognize the pattern of native Malay urban architectural and its clearly proven through the 3D GIS Modelling reconstruction that has been performed through both approached of drone and laser scanning data processing. This work in other way shows the effectiveness of geospatial data in safeguarding our cultural heritage simultaneously supporting the mission of sustainable goals developments in local and global.